50th anniversary of the discovery of Feigenbaum's patterns - Kuznetsov, Aleksandr Petrovich; Sedova, Yuliya Viktorovna (Известия высших учебных заведений: Прикладная нелинейная динамика)
In 1975, while experimenting with a pocket programmable calculator, American physicist Mitchell Feigenbaum discovered the universal patterns of transition to chaos through period doubling bifurcations, which now bear his name.